2021
DOI: 10.1042/bst20210112
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the therapeutic inhibition of Cdc42 signalling

Abstract: Cdc42 is a member of the Rho family of small GTPases and a key regulator of the actin cytoskeleton, controlling cell motility, polarity and cell cycle progression. It signals downstream of the master regulator Ras and is essential for cell transformation by this potent oncogene. Overexpression of Cdc42 is observed in several cancers, where it is linked to poor prognosis. As a regulator of both cell architecture and motility, deregulation of Cdc42 is also linked to tumour metastasis. Like Ras, Cdc42 and other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…Many groups have sought to develop small molecules that inhibit PPIs, including between Ras family members and their downstream effectors ( Bery et al, 2018 ; Quevedo et al, 2018 ). While several of these agents have made it to the clinic, others failed secondary to their suboptimal selectivity and off-target effects ( Murphy et al, 2021 ). ARN22089 had single-digit micromolar EC 50 s in a panel of cell lines ( Figure 2D ), consistent with the EC 50 values observed with other RAC/CDC42 family inhibitors ( Maldonado et al, 2020 ) and non-covalent RAS family PPI inhibitors ( Bery et al, 2018 ; Quevedo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many groups have sought to develop small molecules that inhibit PPIs, including between Ras family members and their downstream effectors ( Bery et al, 2018 ; Quevedo et al, 2018 ). While several of these agents have made it to the clinic, others failed secondary to their suboptimal selectivity and off-target effects ( Murphy et al, 2021 ). ARN22089 had single-digit micromolar EC 50 s in a panel of cell lines ( Figure 2D ), consistent with the EC 50 values observed with other RAC/CDC42 family inhibitors ( Maldonado et al, 2020 ) and non-covalent RAS family PPI inhibitors ( Bery et al, 2018 ; Quevedo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Cdc42, a member of the Rho GTPase family, which together with other family members, including RhoA, Rac1, Rac2, RhoH, RohD/F, RhoU/V affect cell movement, endocytosis, cell morphology and cell cycle progression through their effects on actin cytoskeletal organization [ 111 , 112 , 113 , 114 , 115 ]. More important, Cdc42, together with Rac1 and RhoA, affect the dynamics of filopodia, lamellipodia and stress fibers, namely their assembly (formation), disassembly and maintenance [ 116 , 117 , 118 , 119 , 120 ].…”
Section: Fak (Focal Adhesion Kinase) and Small Gtpase Cdc42mentioning
confidence: 99%
“…Inhibiting a signalling node protein with functions essential to normal physiology is no small task. There is acknowledgement within the field of the need to identify which subtypes of cancer would benefit from a potent and selective Cdc42 inhibitor if one were available [17]. Nevertheless, the role of Cdc42, in migration and in regulation of specialized invadopodia and extracellular vesicles, positions it at the centre of multiple investigations into cell invasion and metastasis in different cancer types.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Cdc42 participates in the regulation of cytoskeletal and microtubule dynamics, transcription, cell cycle progression, cell polarity, apoptosis, phagocytosis, vesicle trafficking and cell adhesion, leading to roles in tumourigenesis as well as invasion and metastasis. Inhibition of Cdc42 and components of its signalling pathways are therefore attractive therapeutic targets in cancer and are currently the subject of small molecule and biologic based targeting efforts, which we have recently reviewed [17]. Here we review alterations found to Cdc42 itself and to key components of the signal transduction pathways it controls in cancer.…”
Section: Introductionmentioning
confidence: 99%